Epoxy resin composition, epoxy resin composition containing reinforcing fibers, prepreg, thermoplastic resin, and fiber-reinforced plastic
By using thermoplastic epoxy resin compositions and polymerization catalysts within a specific range in fiber reinforced plastics, combined with reinforced fibers, the problem of insufficient impact strength of existing fiber reinforced plastics is solved, and efficient impact characteristics are achieved.
Patent Information
- Application Number
- CN202411117712.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-28
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-28
AI Technical Summary
Existing fiber reinforced plastics have shortcomings in impact strength, especially the impact strength of thermally hardened epoxy resins is relatively low, making it difficult to meet certain applications with high impact resistance requirements.
By using a thermoplastic epoxy resin composition with an absolute molecular weight of 50,000 to 100,000 to 100,000, the slope α of the range 0.45 or more and 0.80 or less in the range of 0.80 or less in the Mark-Houwink-Sakurada (M-H) was used to form a high molecular weight phenoxy resin to improve the impact characteristics of the fiber-reinforced thermoplastic resin.
It achieves excellent impact characteristics of fiber-reinforced thermoplastic resin, and provides a fiber-reinforced plastic with excellent impact characteristics, suitable for applications requiring high impact resistance.
Smart Images

Figure CN119529236A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin, an epoxy resin composition, an epoxy resin composition containing reinforcing fibers, a prepreg, and fiber-reinforced plastics using the same. Background Art
[0002] In recent years, there has been a demand for further improvement in impact resistance for components used in electronic devices, battery cases, motor protection tubes, mobile structures, sporting goods, prosthetic limbs and feet, and the like.
[0003] Fiber reinforced plastics (FRP) exhibit excellent physical properties such as light weight and high strength. Among them, plastics made using carbon fibers as reinforcing fibers (carbon fiber reinforced plastics (CFRP)) are known for their particularly excellent mechanical strength.
[0004] Among CFRPs, materials using thermoplastic resin as a base resin are called carbon fiber reinforced thermoplastic plastics (CFRTP), and are expected to have excellent secondary processability and recyclability.
[0005] It is known that the impact strength of conventional thermosetting epoxy resin is 5 kJ / m 2 Non-patent document 1 shows that the impact strength of CFRP with epoxy resin as the base material is 200 kJ / m 2 (Notched Charpy impact test) approx.
[0006] It is known that polycarbonate is 80kJ / m 2 (Notched Charpy impact test) shows excellent impact strength, but Non-Patent Document 2 shows that the impact strength of CFRTP with polycarbonate as the base resin is 150 kJ / m 2 about.
[0007] In order for CFRP to exhibit sufficient impact strength, it is necessary to increase the impact strength of the matrix resin and also ensure the adhesion between the fiber and the resin interface.
[0008] As the parent material (matrix) resin of FRP, epoxy resin is mainly used due to its excellent balance between price and physical properties. Among them, Patent Document 1 proposes the following method: epoxy resin and a compound containing phenolic hydroxyl group are mixed with reinforcing fibers in advance, and polymerization is carried out by addition polymerization using a polymerization catalyst and a reaction retarder, so as to form a fiber-reinforced thermoplastic resin. In Patent Document 2, the following situation is proposed: a difunctional epoxy resin is subjected to an addition polymerization reaction with a difunctional compound having a functional group selected from the group consisting of phenolic hydroxyl group, amino group, carboxyl group, mercapto group, isocyanate group and cyanate group. This kind of epoxy resin is also called an in-situ polymerization type thermoplastic epoxy resin, and the FRP using it is expected to have excellent mass production, molding and recyclability. The in-situ polymerization type thermoplastic epoxy resin is impregnated into the fiber in a low viscosity state before polymerization, so the impregnation is good, the proportion of reinforcing fibers can be increased, and the impact strength or toughness is excellent compared with the case of using a general-purpose thermosetting epoxy resin.
[0009] For example, Patent Document 3 discloses a method for obtaining a phenoxy resin having a large degree of branching by reacting a phenoxy resin which is a thermoplastic resin in the presence of an organic phosphonium salt catalyst.
[0010] Here, non-patent document 3 shows that the branch structure of the resin affects the mechanical properties, and that the branch structure can be evaluated by using light scattering gel permeation chromatography (GPC). Non-patent document 4 shows a method of connecting a refractive index (RI) detector or a viscosity detector in series with light scattering GPC (Gel Permeation Chromatography-Low Angle Light Scatter (GPC-LALS)) to simultaneously analyze.
[0011] It is known that by using the Mark-Houwink-Sakurada diagram (MH diagram) for sorting, the slope α of the diagram can be used to evaluate the branching structure. The closer the value of α is to 1, the less branches it is a straight-chain structure. In non-patent literature 5 and non-patent literature 6, a method using α as an index is shown as an evaluation of the degree of branching. In particular, Fig. 4 of non-patent literature 6 is a graph in which the intrinsic viscosity (η) is plotted in double logarithmic form (MH diagram) against the absolute molecular weight (M).
[0012] [Prior art literature]
[0013] [Patent Document]
[0014] [Patent Document 1] Japanese Patent Application Publication No. 2006-321897
[0015] [Patent Document 2] International Publication No. 2004 / 060981
[0016] [Patent Document 3] Japanese Patent Application Publication No. 2017-171802
[0017] [Non-patent literature]
[0018] [Non-patent document 1] Journal of the Society of Materials Science, Japan, Vol. 43, No. 487, pp. 482-488, April 1994
[0019] [Non-patent document 2] Journal of the Society of Materials Science, Japan, Vol. 60, No. 3, pp. 251-258, Mar. 2011
[0020] [Non-patent document 3] Polymer, Vol. 30, July (1981), P540-P545
[0021] [Non-patent document 4] Journal of the Rubber Association of Japan, Vol. 60, No. 11 (1987), P636-P643
[0022] [Non-patent document 5] Thermosetting resin, Vol. 6, No. 3 (1985), P127-P134
[0023] [Non-patent document 6] Starch Science, Vol. 36, No. 4 (1989), P257-P264 Summary of the invention
[0024] [Problems to be solved by the invention]
[0025] The present invention aims to provide an in-situ polymerization type epoxy resin composition and a prepreg suitable for in-situ polymerization type fiber-reinforced thermoplastic resin and for obtaining a fiber-reinforced thermoplastic resin having excellent impact properties.
[0026] [Technical means to solve the problem]
[0027] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that a fiber-reinforced thermoplastic resin having excellent impact properties can be obtained by using a linear thermoplastic epoxy resin having a small degree of branching and a slope α of 0.45 or more and 0.80 or less in the range of an absolute molecular weight (M) of 50,000 to 100,000 in a Mark-Houwink-Sakurada plot (MH plot), thereby completing the invention.
[0028] That is, the present invention is an epoxy resin composition, comprising an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups reactive with the epoxy groups in one molecule, and a polymerization catalyst (D) as essential components, and the epoxy resin composition becomes a thermoplastic resin through a polymerization reaction, wherein
[0029] The amount of the epoxy resin (A) and the compound (B) is 0.90 mol to 1.10 mol of the compound (B) per 1 mol of the epoxy resin (A).
[0030] In the thermoplastic resin obtained by polymerizing the epoxy resin composition, the slope α in the absolute molecular weight (M) range of 50,000 to 100,000 in the Mark-Houwink-Sakurada plot (MH plot) measured by light scattering GPC is 0.45 or more and 0.80 or less.
[0031] The amount of the polymerization catalyst (D) is preferably 0.01 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the total amount of the epoxy resin (A) and the compound (B).
[0032] When the epoxy resin composition does not contain an organic solvent or contains an organic solvent, the content of the organic solvent is preferably 0.01% by weight or more and 10% by weight or less of the epoxy resin composition so that the epoxy resin (A) and the compound (B) are uniformly dissolved.
[0033] In addition, the present invention is an epoxy resin composition containing reinforcing fibers, wherein the epoxy resin composition and reinforcing fibers (F) are contained. The reinforcing fibers (F) are preferably short fibers or continuous fibers having a length of 1 mm or more. The reinforcing fibers (F) are preferably carbon fibers, preferably contained in a ratio of 20% to 80% by weight.
[0034] The present invention also provides a prepreg including the epoxy resin composition containing reinforcing fibers, a fiber-reinforced plastic using the epoxy resin composition containing reinforcing fibers, and a fiber-reinforced plastic using the prepreg.
[0035] In addition, the present invention is a thermoplastic resin obtained from the epoxy resin composition, wherein the thermoplastic resin has a slope α of 0.45 or more and 0.80 or less at an absolute molecular weight (M) of 50,000 to 100,000 in a Mark-Houwink-Sakurada plot (MH plot) measured by light scattering GPC.
[0036] The present invention also provides a prepreg comprising the thermoplastic resin and reinforcing fiber (F), a fiber-reinforced plastic comprising the thermoplastic resin and reinforcing fiber (F), and a fiber-reinforced plastic using the prepreg.
[0037] [Effects of the Invention]
[0038] The thermoplastic resin obtained from the epoxy resin composition of the present invention has excellent impact properties, and can provide a fiber reinforced plastic (FRTP) having excellent impact properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The MH chart of the polymer obtained in Example 1 is shown. Here, the vertical axis is the logarithm of the intrinsic viscosity (η), and the horizontal axis is the logarithm of the absolute molecular weight (M). DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in detail in conjunction with preferred embodiments of the present invention.
[0041] The epoxy resin composition (E) of the present invention is an epoxy resin composition that contains an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups that react with the epoxy groups in one molecule, and a polymerization catalyst (D) as essential components, and becomes a thermoplastic resin through a polymerization reaction. The composition may also contain additives such as reinforcing fibers (F) or organic solvents, fillers, and flame retardants.
[0042] In addition, in this specification, an epoxy resin (A) having two epoxy groups in one molecule is sometimes referred to as "epoxy resin (A)" or "bifunctional epoxy resin (A)". A compound (B) having two functional groups that react with the epoxy groups in one molecule is sometimes referred to as "compound (B)" or "bifunctional compound (B)". In addition, when simply expressed as a "resin composition", it refers to both an "epoxy resin composition" and an "epoxy resin composition containing reinforcing fibers".
[0043] In the thermoplastic resin obtained by polymerizing the epoxy resin composition, the slope α at an absolute molecular weight (M) of 50,000 to 100,000 in the Mark-Houwink-Sakurada plot (MH plot) measured by light scattering GPC is 0.45 or more and 0.80 or less.
[0044] The thermoplastic resin obtained by polymerizing the epoxy resin composition is a high molecular weight phenoxy resin. The branching structure of the phenoxy resin is evaluated by the slope α of the MH graph at an absolute molecular weight (M) of 50,000 to 100,000. The closer the value of α is to 0, the closer it is to a spherical structure with a large number of branches, and the closer it is to 1, the less branched it is a linear structure.
[0045] Regarding the evaluation of branches, the slope α of the MH graph adopts a value in the range of 50,000 to 100,000 absolute molecular weights (M). In the region where the absolute molecular weight (M) is less than 50,000, the difference in the slope based on the degree of branching is small, which is not suitable for the evaluation of the degree of branching. In the region where the molecular weight is more than 100,000, since the volume occupied in the molecular weight distribution decreases, it is not suitable to use it as an evaluation value.
[0046] The slope α of the MH diagram is 0.45 or more, more preferably 0.47 or more, and further preferably 0.50 or more. When the slope α is less than the lower limit of the range, there are a large number of branched structures and the impact strength cannot be fully demonstrated. Although there is no preferred upper limit of the slope α, it is usually 0.80 or less in the case of phenoxy resins.
[0047] The slope α of the MH diagram is measured using the following measuring device and measuring conditions. The existence ratio of the molecules (area of each small interval / area of the entire peak) is calculated using an RI detector, the absolute molecular weight (M) of each small interval is analyzed using a light scattering detector, and the intrinsic viscosity (η) is analyzed using a viscosity detector. An MH diagram is prepared based on the values of the absolute molecular weight (M) and the intrinsic viscosity (η), and the slope α in the range of absolute molecular weight (M) of 50,000 to 100,000 is calculated.
[0048] Measuring device: OMNISEC (manufactured by Malvern)
[0049] Column: TSK gel guard column MP (XL) + TSK gel multipore HXL-M + TSK gel G1000HXL (all manufactured by Tosoh Corporation) connected in series
[0050] Detector: Differential refractive index detector (RI detector) + light scattering detector (Right Angle Light Scattering (RALS) 90°, LALS 7°) + viscosity detector
[0051] Data processing: OMNISEC-11.10 (manufactured by Malvern)
[0052] Measurement conditions: column temperature 40°C
[0053] Development solvent: Tetrahydrofuran (THF)
[0054] Flow rate 1.0mL / min
[0055] Sample: A THF solution prepared by dissolving 0.02 g of the hardened product in 10 mL of THF was filtered through a 0.20 μm microfilter (100 μL).
[0056] The weight average molecular weight (Mw) of the thermoplastic resin (phenoxy resin) obtained by polymerizing the epoxy resin composition (E) is preferably 40,000 or more and 200,000 or less. When the Mw of the thermoplastic resin is less than the lower limit of the range, a large amount of compounds that are not fully polymerized will be included, and there is a concern about deterioration of mechanical strength. On the other hand, when the Mw of the thermoplastic resin exceeds the upper limit of the range, the crosslinking reaction proceeds, and there is a concern about damage to thermoplasticity. Mw is preferably 45,000 or more and 150,000 or less, and more preferably 50,000 or more and 120,000 or less.
[0057] The epoxy equivalent of the thermoplastic resin is preferably 10,000 g / eq. or more. If the epoxy equivalent is less than 10,000 g / eq., there is a concern that polymerization may not proceed sufficiently. The epoxy equivalent is more preferably 20,000 g / eq. or more, and further preferably 25,000 g / eq. or more.
[0058] The glass transition temperature (Tg) of the thermoplastic resin is preferably 90° C. or higher, more preferably 100° C. or higher, and further preferably 120° C. or higher.
[0059] The epoxy resin (A) used in the epoxy resin composition (E) can be preferably an epoxy resin having an epoxy equivalent in the range of 100 g / eq. to 500 g / eq. The lower limit is preferably 150 g / eq., more preferably 180 g / eq. The upper limit is preferably 300 g / eq., more preferably 280 g / eq.
[0060] The purity of epoxy resin (A) is preferably 95% by weight or more. When monofunctional impurities are included in epoxy resin (A), there is a concern that the molecular weight after polymerization will not rise, so there is a concern that the mechanical properties of the obtained thermoplastic resin product will deteriorate. Therefore, the monofunctional impurities are preferably 2% by weight or less relative to epoxy resin (A). When trifunctional or higher impurities are included, it is easy to form a cross-linked structure starting from the impurities, so in addition to the dispersion of the polymer becoming larger, there is also a concern that gelation will damage thermoplasticity. Therefore, for trifunctional or higher impurities, it is preferably 1% by weight or less relative to epoxy resin (A). If the purity of epoxy resin (A) is high, positional isomers or oligomers may also be included. In addition, epoxy resin (A) may be used only one or in combination of multiple types.
[0061] Examples of the epoxy resin (A) include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol E epoxy resins, bisphenol Z epoxy resins, bisphenol S epoxy resins, bisphenol AD epoxy resins, bisphenol acetophenone epoxy resins, bisphenol trimethylcyclohexane epoxy resins, bisphenol fluorene epoxy resins (e.g., ZX-1201 (manufactured by Nippon Steel Chemical & Material Co., Ltd.)), biscresol fluorene epoxy resins (e.g., OGSOL CG-500 (manufactured by Osaka Gas Chemical Co., Ltd.)), tetramethyl bisphenol A epoxy resins, tetramethyl bisphenol F epoxy resins (e.g., YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.)), and tetramethyl bisphenol A epoxy resins. Chemical & Material) Co., Ltd.), tetra-tert-butylbisphenol A type epoxy resin, tetramethylbisphenol S type epoxy resin, dihydroxydiphenyl ether type epoxy resin, thiodiphenol type epoxy resin, tetrabromobisphenol A type epoxy resin and other bisphenol type epoxy resins, or biphenol type epoxy resins, tetramethylbiphenol type epoxy resins (such as YX4000 (Mitsubishi Chemical Co., Ltd.)), dimethylbiphenol type epoxy resins Epoxy resins such as tetra-tert-butylbiphenol epoxy resins, or benzene glycol epoxy resins such as hydroquinone epoxy resins, methyl hydroquinone epoxy resins, dibutyl hydroquinone epoxy resins, resorcinol epoxy resins, and methyl resorcinol epoxy resins, or dihydroxyanthracene epoxy resins, hydrogen anthracene hydroquinone epoxy resins, dihydroxynaphthalene epoxy resins, bis-naphthol fluorene epoxy resins, and diphenyl dicyclopentadiene epoxy resins.
[0062] It is particularly preferred to include an epoxy resin (a) represented by the following general formula (1). In the above case, it is preferred that the epoxy resin (A) contains 50% by weight or more, more preferably 66% by weight or more, further preferably 75% by weight or more, and particularly preferably 80% by weight or more. The epoxy resin (a) constitutes a part of the epoxy resin (A).
[0063] [Chemistry 1]
[0064]
[0065] In formula (1), A is a divalent group represented by the following formula (2): n is a repetition number and its average value is 0 to 5, preferably 0.1 to 1.
[0066] [Chemistry 2]
[0067]
[0068] In formula (2), X is any one of a single bond, a hydrocarbon group having 1 to 13 carbon atoms, -O-, -CO-, -COO-, -S-, and -SO2-.
[0069] The hydrocarbon group having 1 to 13 carbon atoms is preferably an alkylene group having 1 to 9 carbon atoms or an arylene group having 6 to 13 carbon atoms, and examples thereof include -CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -CHPh-, -C(CH3)Ph-, 1,1-cyclopropylene, 1,1-cyclobutylene, 1,1-cyclopentylene, 1,1-cyclohexylene, 4-methyl-1,1-cyclohexylene, 3,3,5-trimethyl-1,1-cyclohexylene, 1,1-cyclooctylene, 1 , 1-cyclononylene, 1,2-ethylene, 1,2-cyclopropylene, 1,2-cyclobutylene, 1,2-cyclopentylene, 1,2-cyclohexylene, 1,2-phenylene, 1,3-propylene, 1,3-cyclobutylene, 1,3-cyclopentylene, 1,3-cyclohexylene, 1,3-phenylene, 1,4-butylene, 1,4-cyclohexylene, 1,4-phenylene, 1,1-fluorenyl, 1,2-xylylene, 1,4-xylylene, tetrahydrodicyclopentadienyl, tetrahydrotricyclopentadienyl, etc. In addition, Ph represents a phenyl group.
[0070] Among these, X is preferably a single bond, -O-, -CO-, -COO-, -S-, -SO2-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CHPh-, -C(CH3)Ph-, 1,1-cyclohexylene, 4-methyl-1,1-cyclohexylene, 3,3,5-trimethyl-1,1-cyclohexylene, 1,4-cyclohexylene, 1,4-phenylene, 1,1-fluorenyl, and more preferably a single bond, -O-, -CO-, -COO-, -S-, -SO2-, -CH2-, -CH(CH3)-, -C(CH3)2-, -C(CH3)Ph-, 1,1-cyclohexylene, 3,3,5-trimethyl-1,1-cyclohexylene, 1,1-fluorenyl. In addition, Ph represents a phenyl group. The alkylene group has the meaning including the alkylidene group.
[0071] Y 1 Each of the groups is independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0072] Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group.
[0073] Examples of the aryl group having 6 to 10 carbon atoms include phenyl, tolyl, ethylphenyl, xylyl, n-propylphenyl, isopropylphenyl, mesityl, and naphthyl.
[0074] Among these, methyl, ethyl, n-propyl, n-butyl, tert-butyl, phenyl, tolyl, xylyl, or naphthyl is preferred, and methyl, ethyl, n-propyl, n-butyl, tert-butyl, phenyl, or tolyl is more preferred.
[0075] Y 2 Each of the above Y and Y is independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and is preferably a group other than a hydrogen atom. 1 The preferred Y is the same as those exemplified in 2 With Y 1 same.
[0076] Y 3 are independently any one of a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an aryl group having 6 to 10 carbon atoms. 1 The preferred Y is the same as those exemplified in 3 A hydrogen atom or Y 1 same.
[0077] Examples of the epoxy resin (a) include tetramethylbisphenol F epoxy resins, tetramethylbiphenol epoxy resins, biscresol fluorene epoxy resins, etc. The epoxy resin (a) may be used alone or in combination of two or more.
[0078] The epoxy equivalent of the epoxy resin (a) is preferably 150 g / eq. to 350 g / eq. The purity of the epoxy resin (a) is preferably 95% by weight or more.
[0079] The bifunctional compound (B) used in the epoxy resin composition (E) may be any one of a diphenol compound (B1) having two hydroxyl groups bonded to an aromatic ring, a diester compound (B2) having two acyloxy groups bonded to an aromatic ring, or a monoester compound (B3) having one hydroxyl group and one acyloxy group bonded to an aromatic ring. In addition, the diester compound (B2) and the monoester compound (B3) are sometimes referred to as "ester compounds" without distinguishing between them. Among these, the diphenol compound (B1) is preferred.
[0080] The difunctional compound (B) may preferably have a hydroxyl equivalent or ester equivalent of 80 g / eq. or more and 500 g / eq. or less. The lower limit is preferably 100 g / eq., more preferably 110 g / eq. The upper limit is preferably 300 g / eq., more preferably 250 g / eq.
[0081] The physical property values of the difunctional compound (B), i.e., the specific values of the hydroxyl equivalent or ester equivalent, softening point or melting point, can be obtained from the supplier catalog of the commercially available material. In addition, the hydroxyl equivalent or ester equivalent can be calculated based on the feed ratio, or can also be measured according to the Japanese Industrial Standards (JIS) K0070 specification. The softening point can also be measured by the ring and ball method described in JIS K7234-1986. The melting point can also be measured by the method described in JIS K0064-1992, or by using a differential scanning calorimeter.
[0082] The purity of the difunctional compound (B) is preferably 95% by weight or more. In the case of containing monofunctional impurities, there is a concern that the molecular weight after polymerization will not increase, so there is a concern that the mechanical properties of the manufactured thermoplastic resin will deteriorate. Therefore, the monofunctional impurities are preferably 2% by weight or less relative to the difunctional compound (B). In the case of containing trifunctional or higher impurities, since it is easy to form a cross-linked structure with the impurities as the starting point, in addition to the concern that the dispersion of the polymer becomes larger, there is also a concern that gelation will damage the thermoplasticity. Therefore, with respect to trifunctional or higher impurities, it is preferably 1% by weight or less relative to the difunctional compound (B). If the purity of the difunctional compound (B) is high, positional isomers may also be included. In addition, the difunctional compound (B) may be used only one or in combination. In addition, the acyloxy group is represented by R-CO-O-, R is a hydrocarbon group with 1 to 19 carbon atoms, and may also contain heteroatoms such as oxygen atoms (O), sulfur atoms (S), and nitrogen atoms (N). The hydrocarbon group having 1 to 19 carbon atoms is preferably an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, an aralkyl group having 7 to 13 carbon atoms, or an unsaturated heterocyclic group having 4 to 19 carbon atoms.
[0083] The alkyl group having 1 to 12 carbon atoms may be any of a linear, branched, or cyclic group, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, and a cyclododecyl group.
[0084] Examples of the aryl group having 6 to 12 carbon atoms include phenyl, tolyl, ethylphenyl, xylyl, n-propylphenyl, isopropylphenyl, mesityl, naphthyl, and methylnaphthyl.
[0085] Examples of the aralkyl group having 7 to 13 carbon atoms include benzyl, methylbenzyl, dimethylbenzyl, trimethylbenzyl, phenethyl, 2-phenylisopropyl, and naphthylmethyl.
[0086] Examples of the unsaturated heterocyclic group having 4 to 19 carbon atoms include a furyl group having 4 carbon atoms, a thienyl group having 4 carbon atoms, a pyran skeleton substituent group having 5 carbon atoms, a thiopyran skeleton substituent group, and a pyridyl group, azanaphthyl group, and azaanthryl group having 5 to 12 carbon atoms.
[0087] Among these, an acyloxy group having a hydrocarbon group having 1 to 7 carbon atoms or an unsaturated heterocyclic group having 4 to 12 carbon atoms is preferred, an acetoxy group, a propionyloxy group, a butyryloxy group, a benzoyloxy group, a methylbenzoyloxy group, a furyl group, a thienyl group, and a pyridyl group are more preferred, an acetoxy group, a benzoyloxy group, a furyl group, and a thienyl group are further preferred, and an acetoxy group and a furyl group are particularly preferred.
[0088] Examples of the diphenol compound (B1) include bisphenol A, bisphenol F, bisphenol E, bisphenol Z, 2,4′-bisphenol S, bisphenol AP, bisphenol C, bisphenol acetophenone, bisphenol trimethylcyclohexane, tetramethylbisphenol A, tetramethylbisphenol F, tetra-tert-butylbisphenol A, dihydroxydiphenyl ether, dihydroxydiphenylmethane, thiodiphenol, dihydroxystilbene and the like bisphenol compounds; hydroquinone, methylhydroquinone, dibutylhydroquinone, resorcinol, methylresorcinol and the like benzene glycol compounds; dihydroxynaphthalene, diphenylphosphinohydroquinone and the like phenol compounds containing phosphorus; and the like.
[0089] In particular, when used in an epoxy resin composition containing reinforcing fibers, bisphenol compounds are preferred. In addition, phosphorus-containing phenol compounds may also be used for the purpose of imparting flame retardancy.
[0090] As diester compounds (B2) and monoester compounds (B3), compounds in which two or one of the hydroxyl groups of the diphenol compound (B1) are replaced by acyloxy groups (active esters) can be cited. The diester compound (B2) is obtained by acylation of the diphenol compound (B1) by a condensation reaction with an acylating agent such as an organic acid anhydride, an organic acid halide or an organic acid. The monoester compound (B3) can also be obtained by separating from a mixture of a monoester compound (B3), a diester compound (B2), and a diphenol compound (B1) obtained by adjusting the molar ratio of the acylating agent during the acylation of the diphenol compound (B1). Due to the acylation, the melting point of the compound is reduced. Therefore, it is expected that the compatibility with the epoxy resin will be improved.
[0091] As the acid component used for the acylation, for example, organic acids such as acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, octanoic acid, caprylic acid, lauric acid, stearic acid, oleic acid, benzoic acid, tert-butylbenzoic acid, hexahydrobenzoic acid, phenoxyacetic acid, acrylic acid, methacrylic acid, furancarboxylic acid, thiophenecarboxylic acid, and pyridinecarboxylic acid, or anhydrides of organic acids, or halides of organic acids, or esters of organic acids can be used.
[0092] Examples of the anhydride of the organic acid include acetic anhydride, benzoic anhydride, phenoxyacetic anhydride, bis(2-furancarboxylic acid) anhydride, and bis(2-thiophenecarboxylic acid) anhydride.
[0093] Examples of organic acid esters include methyl acetate, ethyl acetate, butyl acetate, methyl benzoate, ethyl benzoate, etc. Examples of organic acid halides include acetic acid chloride, benzoic acid chloride, phenoxyacetic acid chloride, 2-furancarboxylic acid chloride, and 2-thiophene acid chloride.
[0094] As these acylating agents, preferred are halides of organic acids such as acetic acid chloride, benzoic acid chloride, phenoxyacetic acid chloride, 2-furancarboxylic acid chloride, and 2-thiophene acid chloride, or anhydrides of organic acids such as acetic anhydride, benzoic acid anhydride, phenoxyacetic acid anhydride, and bis(2-furancarboxylic acid) anhydride. In terms of eliminating the need for post-esterification water washing and avoiding the incorporation of halogens that are disliked in electrical material applications, more preferred are anhydrides such as acetic anhydride, benzoic anhydride, and bis(2-furancarboxylic acid) anhydride, and further preferred are acetic anhydride and bis(2-furancarboxylic acid) anhydride.
[0095] In the epoxy resin composition (E), the ratio of the bifunctional compound (B) is 0.90 mol to 1.10 mol, preferably 0.95 mol to 0.99 mol, and more preferably 0.97 mol to 0.98 mol, based on 1.00 mol of the bifunctional epoxy resin (A).
[0096] In the epoxy resin composition (E), the difunctional epoxy resin (A) and the difunctional compound (B) react in sequence, and thermoplasticity is exhibited by adopting a linear structure. If the difunctional epoxy resin (A) is excessive, the polymer becomes epoxy-terminated, and if the difunctional compound (B) is excessive, the polymer becomes phenol-terminated or acyl-terminated, and the reaction is terminated.
[0097] When the ratio of the difunctional compound (B) exceeds 0.99 mol, the polymer becomes a phenolic terminal or an acyloxy terminal and the reaction is terminated, so there is a concern that it is difficult to increase the molecular weight. On the other hand, when the ratio of the difunctional compound (B) is less than 0.95 mol, the excess epoxy group undergoes a side reaction, thereby causing a concern that the polymer gels and loses thermoplasticity.
[0098] In addition, since the difunctional epoxy resin (A) is difunctional, its molecular weight is equivalent to a value twice the epoxy equivalent. Similarly, the molecular weight of the difunctional compound (B) is also equivalent to a value twice the functional group (hydroxyl, acyl) equivalent. Therefore, the molar ratio of the difunctional compound (B) to the difunctional epoxy resin (A) is the same as the equivalent ratio of the functional group (hydroxyl, acyl) of the difunctional compound (B) to the epoxy group of the difunctional epoxy resin (A).
[0099] Examples of the diester compound (B2) include compounds represented by the following formula (3).
[0100] [Chemistry 3]
[0101]
[0102] In formula (3), X, Y 1 , Y 2 , Y 3 Same as in formula (2).
[0103] The diester compound (B2) may be a phosphorus-containing compound. Examples of the phosphorus-containing compound include a cyclic phosphorus-containing compound represented by the following formula (4) (diacetylated product of 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ)).
[0104] [Chemistry 4]
[0105]
[0106] When using a phosphorus-containing epoxy resin or a phosphorus-containing difunctional compound, the phosphorus content when imparting flame retardancy to the epoxy resin composition (E) is preferably 1% by weight or more and 6% by weight or less, more preferably 1.5% by weight or more and 5% by weight or less, and further preferably 2% by weight or more and 4% by weight or less, relative to 100% by weight of the total amount of the epoxy resin (A) and the compound (B). In addition, it is also possible to not mix a phosphorus-containing compound as the difunctional epoxy resin (A) or the difunctional compound (B) in the epoxy resin composition (E), or to mix various known phosphorus-containing compounds other than these.
[0107] In addition, if the amount of impurities that do not have an active group that reacts with either the bifunctional epoxy resin (A) or the bifunctional compound (B) and do not inhibit the polymerization reaction when in the form of a monomer, such as non-reactive impurities derived from raw materials, increases, there is a concern that the molecular weight after polymerization will decrease. Therefore, such impurities are preferably 2% by weight or less with respect to either the bifunctional epoxy resin (A) or the bifunctional compound (B).
[0108] In the epoxy resin composition (E), it is preferred that the epoxy resin (A) and the compound (B) are uniformly dissolved. If the compound (B) exists in a crystalline state in the epoxy resin (A), the molar ratio deviates from the design during microscopic observation. If the reaction is started in the state, the polymerization is sometimes not fully carried out. In order to make the polymerization fully proceed, it is preferred that the epoxy resin composition (E) in which the compound (B) and the epoxy resin (A) are uniformly compatible with each other. In addition, the epoxy resin composition (E) before the deployment of the reinforcing fiber, etc. is ideally completely compatible or becomes a uniform liquid. For example, in a state without bubbles, the molten mixture is placed in a glass culture dish in a manner of becoming a thickness of 2mm, and the haze value in the thickness direction is measured. In the case, if the haze value in the thickness direction is less than 30%, it can be judged that it is dissolved to a level that does not affect the polymerization reaction or becomes a uniform liquid.
[0109] In order to obtain an epoxy resin composition (E) in which compound (B), epoxy resin (A) and polymerization catalyst (D) are uniformly compatible with each other, heating can be used to make them compatible. As a method for making them compatible by heating, there is a method of heating a mixture (M) of epoxy resin (A) and compound (B) containing a polymerization catalyst (D), or a method of adding a polymerization catalyst (D) after obtaining an epoxy resin composition (C) obtained by heating a mixture (M) of epoxy resin (A) and compound (B) not containing a polymerization catalyst and making them uniformly compatible. When the mixture (M) of epoxy resin (A) and compound (B) containing a polymerization catalyst (D) is heated to a temperature at which compound (B) is compatible, there is a concern that the polymerization reaction will run away. In the method of heating the mixture (M) of epoxy resin (A) and compound (B) not containing a polymerization catalyst (D), the reaction will not proceed, but in the absence of a catalyst, due to the excessive thermal history, a by-product of a multifunctional component that serves as the basis for branching will be generated, and there is a concern that the branching degree of the polymer will increase. Therefore, it is preferable to adopt a method in which, when obtaining the epoxy resin composition (E), a polymerization catalyst (D) is added after obtaining the epoxy resin composition (C) in which a mixture of the compound (B) and the epoxy resin (A) is heated in advance through a minimum thermal history to be uniformly compatible.
[0110] As the polymerization catalyst (D) that can be used in the present invention, for example, there can be mentioned: N-substituted aminopyridine compounds, phosphine compounds, quaternary phosphonium salt compounds, imidazole compounds, tertiary amine compounds, etc. These polymerization catalysts (D) can be used alone or in combination. Among them, N-substituted aminopyridine compounds and phosphine compounds are particularly preferred.
[0111] As the N-substituted aminopyridine compound that can be used in the present invention, an N-substituted aminopyridine compound represented by formula (5) is preferred.
[0112] [Chemistry 5]
[0113]
[0114] In formula (1), R 1 and R 2 are independently a hydrocarbon group having 1 to 12 carbon atoms, and R 1 With R 2 They can be bonded to each other to form a heterocyclic ring, and the bonding bonds may be -O-, -NH-, or -NR 4 -. Among them, R 4 It is a hydrocarbon group having 1 to 12 carbon atoms, and preferably an alkyl group having 1 to 3 carbon atoms.
[0115] Examples of the hydrocarbon group having 1 to 12 carbon atoms include an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms.
[0116] The alkyl group having 1 to 12 carbon atoms may be any of a linear, branched, or cyclic group, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, and a cyclododecyl group.
[0117] Examples of the aryl group having 6 to 12 carbon atoms include phenyl, o-tolyl, m-tolyl, p-tolyl, ethylphenyl, styryl, xylyl, n-propylphenyl, isopropylphenyl, mesityl, ethynylphenyl, naphthyl, and vinylnaphthyl.
[0118] Examples of the aralkyl group having 7 to 12 carbon atoms include benzyl, methylbenzyl, dimethylbenzyl, trimethylbenzyl, phenethyl, 2-phenylisopropyl, and naphthylmethyl.
[0119] R 1 and R 2 It is preferably an alkyl group having 1 to 3 carbon atoms, or a group having a cyclopentane ring or a cyclohexane ring formed by bonding to each other.
[0120] R 3 Each of the hydrocarbon groups has 1 to 12 carbon atoms, and is preferably an alkyl group having 1 to 3 carbon atoms. Examples of the hydrocarbon group having 1 to 12 carbon atoms include: 1 and R 2 The exemplified base.
[0121] k represents a substituent R 3 The number is an integer from 0 to 4, preferably 0 or 1, and more preferably 0.
[0122] The substitution position of the N-substituted amino group may be any of the 2-position, 3-position, and 4-position of pyridine, but is preferably the 4-position, and more preferably a compound represented by the following formula (5A).
[0123] [Chemistry 6]
[0124]
[0125] In the formula, R 1 and R 2 R 1 and R 2 Synonymous.
[0126] Examples of the N-substituted aminopyridine compounds include 2-dimethylaminopyridine, 2-pyrrolidinylpyridine, 2-(dimethylamino)-6-methylpyridine, 2-methylethylaminopyridine, 2-methylbutylaminopyridine, 2-diethylaminopyridine, 2-methylpropylaminopyridine, 2-pyrrolidinyl-4-methylpyridine, 2-pyrrolidinyl-5-methylpyridine, 2-pyrrolidinyl-6-methylpyridine, 2-morpholinylpyridine, 3-dimethylaminopyridine, N,N-diethyl-3-pyridylamine, 4-dimethylaminopyridine, 4-diethylaminopyridine, 4-dipropylaminopyridine, 4-dibutylaminopyridine, 4-dibenzylaminopyridine, 4-dihexylaminopyridine, 4-dioctylaminopyridine, 4-dinonylaminopyridine, 4-didecylaminopyridine, 4-undecane 4-(dimethylamino)pyridine, 2-methyl-4-(dimethylamino)pyridine, 2-ethyl-4-(dimethylamino)pyridine, 2-phenyl-4-(dimethylamino)pyridine, 3-methyl-4-(dimethylamino)pyridine, 3-ethyl-4-(dimethylamino)pyridine, 3-phenyl-4-(dimethylamino)pyridine, 3,5-dimethyl-4-(dimethylamino)pyridine, 2,5-di-tert-butyl-4-(dimethylamino)pyridine, 1-(pyridin-4-yl)azoane, and the like.
[0127] These N-substituted aminopyridine compounds may be used alone or in combination of two or more.
[0128] Among these N-substituted aminopyridine compounds, preferred are 4-dimethylaminopyridine, 4-diethylaminopyridine, 4-dipropylaminopyridine, 4-dibutylaminopyridine, 4-dibenzylaminopyridine, 4-dihexylaminopyridine, 4-dioctylaminopyridine, 4-dinonylaminopyridine, 4-didecylaminopyridine, 4-undecylaminopyridine, 4-dodecylaminopyridine, 4-diphenylaminopyridine, 4-pyrrolidinylpyridine, 4-piperidinylpyridine, 4-(4-methylpiperidinyl)pyridine, 4-morpholinylpyridine, 4-methylethylaminopyridine, 4-methylpropylaminopyridine, 4-methylbenzylaminopyridine, and 4-methylphenylaminopyridine.
[0129] Among them, more preferred are 4-(dimethylamino)pyridine (the following formula (5a)), 4-pyrrolidinylpyridine (the following formula (5b)), 4-piperidinylpyridine (the following formula (5c)), 4-(4-methylpiperidinyl)pyridine (the following formula (5d)), 4-morpholinylpyridine (the following formula (5e)), and 4-piperazinylpyridine (the following formula (5f)), and further preferred are 4-(dimethylamino)pyridine, 4-pyrrolidinylpyridine, and 4-piperazinylpyridine.
[0130] [Chemistry 7]
[0131]
[0132] Examples of the phosphine-based compound include triphenylphosphine, tri(p-tolyl)phosphine, tri(o-tolyl)phosphine, and tri(p-methoxyphenyl)phosphine.
[0133] Examples of quaternary phosphonium salt compounds include tributyl (methyl) phosphonium-dimethyl phosphate, tributyl (ethyl) phosphonium-diethyl phosphate, methyl tributyl phosphonium-dimethyl phosphate (e.g., Hishicolin PX-4MP (manufactured by Nippon Chemical Industry Co., Ltd.)), methyl trioctyl phosphonium-dimethyl phosphate, tetrabutyl phosphonium-O,O-diethylthiodiphosphate (e.g., Hishicolin PX-4ET (manufactured by Nippon Chemical Industry Co., Ltd.)), and the like.
[0134] Examples of the imidazole compound include 4-methylimidazole, Curezol 1B2MZ, Curezol 1B2PZ, and Curezol TBZ (all manufactured by Shikoku Chemicals Co., Ltd.).
[0135] Examples of the tertiary amine compound include triethylamine and tributylamine.
[0136] Alternatively, examples of other polymerization catalysts include crown ether complexes such as 18-crown-6 (18-C-6) / AcOK complex and 18-C-6 / KF complex, and metal chlorides.
[0137] The amount of the polymerization catalyst (D) is 0.01 to 10 parts by weight relative to 100 parts by weight of the total amount other than the D component constituting the epoxy resin composition (for example, the total amount of the epoxy resin (A) and the compound (B), or the total amount including the (S) component when a small amount of solvent (S) is used). In the case of less than 0.01 parts by weight, in-situ polymerization takes time, so there is a concern that productivity is reduced. In addition, there is also a concern that it is deactivated for some reason before the target molecular weight is reached. On the other hand, in the case of more than 10 parts by weight, the polymerization reaction proceeds rapidly, and on the other hand, there is a concern that the storage stability is damaged and the process suitability is problematic. Since it is a component that participates in the reaction but is not incorporated into the skeleton, in addition to the concern that the physical properties after the polymerization are damaged, it is also economically unprofitable because it is expensive. It is preferably 0.05 to 5.0 parts by weight, more preferably 0.1 to 3.0 parts by weight, and further preferably 0.1 to 1.0 parts by weight. The appropriate amount can be selected by comprehensively considering the balance between the usable time and the polymerization time.
[0138] In the epoxy resin composition (E) of the present invention, as a polymerization catalyst (D), other catalysts may be used together with N-substituted aminopyridine compounds. As other catalysts, as long as they are catalysts used in the manufacturing method of epoxy resin known as the "two-stage method", there are no particular restrictions. For example, alkali metal compounds, organophosphorus compounds, tertiary amines, quaternary ammonium salts, cyclic amines, imidazole compounds, etc. may be mentioned. These other catalysts may be used alone or in combination of two or more. In addition, in the case of an epoxy resin composition containing reinforcing fibers, it is preferred that other catalysts are not included.
[0139] The epoxy resin composition (E) preferably does not contain an organic solvent, but may contain an organic solvent as a solvent for the polymerization catalyst (D) or for viscosity adjustment as needed. As an organic solvent, if it is an organic solvent that does not hinder the reaction of the epoxy resin (A) and the compound (B), it is not particularly limited. In terms of the ease of acquisition, it is preferably a hydrocarbon system, a ketone system, and an ether system. Specifically, it can be listed as: toluene, xylene, acetone, methyl ethyl ketone, isobutyl ketone, cyclopentanone, cyclohexanone, diethylene glycol dimethyl ether, etc. However, if there is a large amount of organic solvent in the reaction, the polymerization reaction is hindered. If there is an organic solvent remaining in the polymer, there is a concern that the mechanical properties or heat resistance will deteriorate. Therefore, in the case of an organic solvent, its proportion is 0.01% by weight or more and 10% by weight or less of the epoxy resin composition (E), preferably 4% by weight or less, and more preferably 2% by weight or less. In the case of an organic solvent, the lower limit is not limited, usually 0.01% by weight or more, and more preferably 0.5% by weight or more.
[0140] In order to maintain the impregnation property of the reinforcing fiber, the epoxy resin composition (E) preferably has a low viscosity. The viscosity (Pa·s) when heated to 85°C is 100 or less, preferably 50 or less, more preferably 20 or less, and further preferably 16 or less. The lower limit of the viscosity is 0.1 or more, preferably 1 or more. In addition, the time until the viscosity becomes twice that measured at the initial stage (viscosity doubling time) is preferably 30 minutes or more, more preferably 60 minutes or more.
[0141] The progress of the polymerization of the epoxy resin composition (E) can be judged by the change of the weight average molecular weight of the polymer (thermoplastic resin). When the weight average molecular weight tends to increase, there is a possibility that the polymerization reaction is not completed. In the polymerization conditions for obtaining the thermoplastic resin from the epoxy resin composition, the temperature is preferably 100°C to 200°C, more preferably 150°C to 180°C, and the time is preferably 30 minutes to 2 hours, more preferably within 1 hour.
[0142] The progress of polymerization of the epoxy resin composition containing reinforcing fibers can also be determined by the change in the weight average molecular weight of the polymer. The polymerization conditions for obtaining a fiber-reinforced thermoplastic resin polymer from the epoxy resin composition containing reinforcing fibers are preferably 100° C. to 200° C. and 2 to 5 hours.
[0143] The impact strength of the polymer is preferably 10 kJ / m 2 More preferably, 20 kJ / m 2 More than 40 kJ / m 2 The upper limit is not particularly limited, but is 100 kJ / m 2 about.
[0144] When a phosphorus-containing compound is used as a raw material, the phosphorus content of the polymer is preferably 1 to 6% by weight, more preferably 1.5 to 5% by weight, and still more preferably 2 to 4% by weight.
[0145] The epoxy resin composition (E) may contain additives. Examples of additives include fillers such as fumed silica, flame retardants such as aluminum hydroxide or red phosphorus, modifiers such as core-shell rubber, and viscosity modifiers such as xylene resins. From the perspective of stabilizing the polymerization reaction, it is preferred that the additives be different from the resin phase, and a plasticizer or a compatible flame retardant may also be included within the range that does not affect the reaction.
[0146] The epoxy resin composition (E) becomes a high molecular weight thermoplastic resin (phenoxy resin) by polymerization. The thermoplastic resin is excellent as a resin component of fiber-reinforced plastics.
[0147] The reinforcing fiber-containing epoxy resin composition of the present invention can be obtained by mixing or impregnating the epoxy resin composition (E) with the reinforcing fiber (F). In addition, the prepreg can be obtained as follows.
[0148] The epoxy resin composition (E) is applied to a demoulding treated paper or plastic film, and a demoulding treated covering film is optionally given, so that the epoxy resin composition film can be obtained. About demoulding paper or demoulding plastic film, covering film, known substances can be used, and there is no particular limitation. The thickness of the epoxy resin composition film is specified by the design thickness of the prepreg and the resin ratio, and the usual thickness is more than 1 μm and less than 300 μm. In the case of less than 1 μm, if the reinforcing fiber is not smoothly defibrinated, there is a problem that the mesh of the fiber becomes obvious, and in the case of more than 300 μm, it is difficult to be uniformly impregnated in the reinforcing fiber. Preferably, more than 5 μm and less than 150 μm, more preferably more than 10 μm and less than 100 μm.
[0149] The reinforcing fiber (F) used in the present invention is a fiber for reinforcing plastics such as carbon fiber, aramid fiber, cellulose fiber, basalt fiber, etc., and is not particularly limited. In addition, regarding the form of the fiber, there can be cited unidirectional material (UD) sheets, fabrics, tows, chopped fibers, nonwoven fabrics, papermaking, etc. formed by aligning the fibers, and there is no particular limitation. Among them, from the perspective of impregnation, the thickness of each fiber bundle is 1 mm or less, preferably 0.5 mm or less, and more preferably 0.2 mm or less.
[0150] The epoxy resin composition or prepreg containing reinforcing fibers of the present invention is obtained from the epoxy resin composition and / or epoxy resin composition film and reinforcing fibers. The ratio of reinforcing fibers to epoxy resin composition is preferably 2:8 to 8:2 by weight. In terms of resin content (Rc), it is 20% to 80% by weight, and the proportion of reinforcing fibers can be increased. If necessary, Rc can also be made less than 35% by weight. Regarding the ratio of reinforcing fibers, if there are too few reinforcing fibers, there is a concern that the strength required by the fiber-reinforced material cannot be fully met. If there are too many reinforcing fibers, there is a concern that defects such as voids will occur.
[0151] The fiber reinforced plastic of the present invention can show, as impact strength, preferably 250 kJ / m 2 More preferably 300 kJ / m 2 More than 350 kJ / m 2 The upper limit is not particularly limited, but is 700 kJ / m 2 about.
[0152] [Example]
[0153] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples. Unless otherwise specified, "parts" represent parts by weight, and "%" represents weight %. In addition, the units of various equivalents are all "g / eq.".
[0154] The raw materials, polymerization catalyst, solvent, and reinforcing fibers used in the examples are as follows.
[0155] [Epoxy resin]
[0156] A1: Tetramethylbiphenol type epoxy resin (manufactured by Mitsubishi Chemical Co., Ltd., YX4000, epoxy equivalent 186, melting point 105°C)
[0157] [Chemistry 8]
[0158]
[0159] A2: Tetramethyl bisphenol F type epoxy resin (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., YSLV-80XY, epoxy equivalent 192, melting point 81°C)
[0160] [Chemistry 9]
[0161]
[0162] A3: Bisphenol A epoxy resin (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., YD-8125, epoxy equivalent 172, melting point 42°C)
[0163] [Chemistry 10]
[0164]
[0165] [Phenol compounds, ester compounds]
[0166] B1: Bisphenol A (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., hydroxyl equivalent 114, melting point 158°C)
[0167] [Chemistry 11]
[0168]
[0169] B2: 4,4'-bis(3,3,5-trimethylcyclohexylene)bisphenol (produced by Honshu Chemical Industry Co., Ltd., BisP-HTG, hydroxyl equivalent 155, melting point 206°C)
[0170] [Chemistry 12]
[0171]
[0172] B3: 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., HCA-HQ, hydroxyl equivalent 162, melting point 250° C.), used as a raw material in Synthesis Example 1.
[0173] [Chemistry 13]
[0174]
[0175] B4: the difunctional acetylated compound obtained in Synthesis Example 1 (10-(2,5-diacetoxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, phosphorus content 7.6%, acetyl equivalent 204, melting point 140°C)
[0176] [Chemistry 14]
[0177]
[0178] [Polymerization catalyst]
[0179] D1: 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd., DMAP)
[0180] [Chemistry 15]
[0181]
[0182] D2: Tri(p-methoxyphenyl)phosphine (manufactured by Beixing Chemical Industry Co., Ltd., TPAP)
[0183] [Chemistry 16]
[0184]
[0185] D3: methyl tributylphosphonium dimethyl phosphate (manufactured by Nippon Chemical Industry Co., Ltd., Hishicolin PX-4MP)
[0186] [Chemistry 17]
[0187]
[0188] D4: 2,3-dihydro-1H-pyrrolo-[1,2-a]benzimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., Curezol TBZ)
[0189] [Chemistry 18]
[0190]
[0191] D5: Tri-o-tolylphosphine (manufactured by Beixing Chemical Industry Co., Ltd., TOTP)
[0192] [Chemistry 19]
[0193]
[0194] [other]
[0195] S: Cyclohexanone
[0196] F: Polyacrylonitrile (PAN) carbon fiber (Toray Corporation, Torayca T700-12K-60E)
[0197] The evaluation methods in the examples are as follows.
[0198] (1) Epoxy equivalent:
[0199] The measurement was performed according to JIS K7236, and the unit is expressed as "g / eq." Specifically, a potentiometric titrator (manufactured by Hiranuma Sangyo Co., Ltd., COM-1600ST) was used, chloroform was used as a solvent, tetraethylammonium bromide acetic acid solution was added, and 0.1 mol / L perchloric acid-acetic acid solution was used.
[0200] (2) Glass transition temperature (Tg):
[0201] The measurement was carried out in accordance with JIS K7121. Specifically, a differential scanning calorimeter EXSTAR6000 DSC6200 (manufactured by Hitachi High-Tech Sciences, Ltd.) was used to measure two cycles in the range of 20°C to 200°C under a temperature increase condition of 10°C / min, and the glass transition temperature (Tmg; the middle temperature of the variation curve relative to the tangent line of the glass state and the rubber state) at the middle point of the measurement graph obtained in the second scan was expressed.
[0202] (3) Weight average molecular weight (Mw) based on absolute molecular weight measurement method (viscometry method) and slope α (branching degree) of MH diagram
[0203] It is determined by light scattering GPC measurement. Specifically, a device in which a TSK gel guard column (TSKgel guardcolumn) MP (XL), TSK gel multipore (TSKgel Multipore) HXL-M, and TSKgel G1000HXL (all manufactured by Tosoh Co., Ltd.) are connected in series with the main body OMNISEC (manufactured by Malvern) is used, and the column temperature is set to 40°C. In addition, tetrahydrofuran (THF) is used as the eluent, and the flow rate is set to 1.0 mL / min. The detectors are differential refractive index detectors (RI detectors), light scattering detectors (RALS 90°, LALS 7°), and viscosity detectors. The measurement sample is a substance obtained by dissolving 0.02 g of the hardened material in 10 mL of THF and filtering it with a 0.20 μm microfilter, and the injection volume is set to 100 μL. In addition, OMNISEC-11.10 (manufactured by Malvern) was used for data processing.
[0204] The weight average molecular weight (Mw) is calculated according to the following procedure. First, the existence ratio of the molecules (area of each micro interval / area of the entire peak) is calculated using the RI detector, and then the absolute molecular weight (M) of each micro interval is detected using a light scattering detector, and the weight average molecular weight (Mw) is calculated based on the relationship between the obtained micro interval and the absolute molecular weight (M).
[0205] The intrinsic viscosity (η) of each micro-range is analyzed by a viscosity detector, and a Mark-Houwink-Sakurada plot (MH plot) is prepared based on the absolute molecular weight (M) and the intrinsic viscosity (η) value, and the slope α (branching degree) in the range of 50,000 to 100,000 absolute molecular weight (M) is obtained. Here, the closer the value of the slope α is to 0, the closer it is to a spherical structure with a large number of branches, and the closer it is to 1, the less branches it has, the more it is a straight chain structure.
[0206] (4) Impact strength:
[0207] The notched Charpy impact test (edge impact) according to the JIS K7111-1 specification was measured. The test machine used was a digital impact tester DG-UB model (manufactured by Toyo Seiki Seisaku-sho Co., Ltd.), and the lift angle was set to 150°. Regarding the hammer, a suitable hammer was selected from hammers with nominal pendulum energies of 0.5J, 1J, 2J, 4J, 7.5J, and 15J. The size of the sample was set to 4mm thick, 80mm long, and 10mm wide, and the notch processing was performed in a way that it became an A notch. (Width of the notch: 8.0mm, radius: 0.25mm). The hammer was swung to the sample, and the impact strength was calculated based on the swing angle of the hammer after measurement.
[0208] Synthesis Example 1 (Ester Compound)
[0209] 162 parts of a bifunctional phenol compound (B3), 105 parts of acetic anhydride, and 79 parts of pyridine were placed in a glass reaction container equipped with a stirrer, a thermometer, a nitrogen gas introduction device, a cooling tube, and a dropping device at room temperature, and the temperature was raised to 60° C. while nitrogen gas was passed and stirred, and the reaction was carried out for 2 hours. Then, the mixture was dried under reduced pressure at 150° C. and 1.3 kPa (10 torr) for 2 hours to obtain 203 parts of a phosphorus-containing compound (B4) represented by the formula (4).
[0210] Example 1
[0211] 144 parts of tetramethylbisphenol epoxy resin (A1), 50 parts of bisphenol A (B1), and 50 parts of 4,4′-bis(3,3,5-trimethylcyclohexylene)bisphenol (B2) were weighed, respectively, and pulverized and mixed using a Henschel mixer to obtain a mixture (M1).
[0212] 100 parts of the mixture (M1) were weighed and melt-mixed using a single-screw extruder (manufactured by IKG Co., Ltd., RMS30-28, L / D=28, full-screw, cylinder temperature 200° C.) with the barrel temperature set at 170° C. The rotation speed was set to 40 rpm so that the residence time in the extruder was 1 minute.
[0213] The entire amount of the molten resin was recovered in a metal can and rapidly cooled to 85° C. to obtain an epoxy resin composition. 0.1 part of 4-dimethylaminopyridine (D1) was added as a polymerization catalyst to 100 parts of the obtained epoxy resin composition, and the mixture was mixed while being heated to 85° C. After mixing, the mixture was rapidly withdrawn and immediately cooled to 20° C. to obtain an epoxy resin composition (E1).
[0214] The obtained epoxy resin composition (E1) was heated and stirred to about 85°C, poured into an iron chrome-plated metal mold container with a gap set to 4 mm in advance, and thermally polymerized at 160°C for 60 minutes in a hot air circulation oven to obtain a polymer (resin plate). The weight average molecular weight of the obtained polymer was measured, and the result was Mw of 79,000, the slope α of the MH diagram in the range of absolute molecular weight (M) 50,000 to 100,000 was 0.53, the epoxy equivalent was 33,000, the Tg was 135°C, and the notched Charpy impact strength was 42 kJ / m 2 .
[0215] The release paper treated with release treatment was fixed on a hot plate preheated to 85°C with the release surface facing upward, and the epoxy resin composition (E1) was placed on the release paper. Then, a bar coater preheated to 85°C was used to coat the epoxy resin composition at a weight of 79 g / m 2 Immediately after coating, the hot plate was removed and air-cooled to obtain an epoxy resin composition sheet.
[0216] Then, on the obtained epoxy resin composition sheet, the fiber area weight was 153 g / m 2 PAN-based carbon fibers (F) were bonded in a manner, and pressure was applied using a hot press preheated to 90° C. so that the surface pressure became 0.5 MPa. After 1 minute, the prepreg was taken out and air-cooled to obtain a prepreg with Rc=34%.
[0217] After stacking 28 sheets of the obtained prepreg so that the orientation direction of the fibers is the same, a release film is attached to the upper and lower surfaces and sandwiched with aluminum plates of 3 mm thickness. After the aluminum plate and the connector that sandwich the prepreg are wrapped with bag film, the connector is connected to a vacuum pump to degas the air in the bag film. The bag film is placed in a hot air circulation oven preheated to 160°C in advance, and cured while maintaining the vacuum state to form a unidirectional fiber reinforced plastic (CFRP plate) with a thickness of 4 mm. In addition, the curing conditions are set to 160°C and 240 minutes. The notched Charpy impact strength of the obtained unidirectional reinforced fiber plastic was measured and the result was 370 kJ / m 2 .
[0218] Example 2 to Example 5, Comparative Example 1 to Comparative Example 3
[0219] The epoxy resin compositions (E2 to E8), polymers, epoxy resin composition sheets, prepregs, and unidirectional reinforced fiber plastics were prepared in the same manner as in Example 1 using the same preparation amounts as in Example 1. In addition, E6 to E8 are comparative examples. When a polymerization catalyst (D2, D4, D5) is added to Example 4 and Comparative Examples 2 to 3, the polymerization catalyst is dissolved in cyclohexanone (S) in advance and then added in a specified amount. In Example 2, the polymerization conditions for the resin plate are set at 180°C and 60 minutes, and the polymerization conditions for the CFRP are set at 180°C and 240 minutes.
[0220] The obtained polymer and unidirectional reinforced fiber plastic were measured for various physical properties in the same manner as in Example 1, and the evaluation results are shown in Table 1. The "molar ratio" in the table indicates the molar ratio (equivalent ratio) of the hydroxyl group of the phenol compound and the acyl group of the ester compound to the epoxy group of the epoxy resin.
[0221] [Table 1]
[0222]
[0223] *1) represents the amount (parts) of component A and component B relative to 100 parts of the mixture.
[0224] [Industrial Applicability]
[0225] The epoxy resin composition of the present invention is effectively used as a matrix resin for fiber reinforced plastics (FRP), and is particularly suitable for use in in-situ polymerization type thermoplastic epoxy resins.
Claims
1. An epoxy resin composition comprising an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups reactive with the epoxy groups in one molecule, and a polymerization catalyst (D) as essential components, and converting into a thermoplastic resin through a polymerization reaction, wherein the epoxy resin composition is characterized in that: The amount of the epoxy resin (A) and the compound (B) is 0.90 mol to 1.10 mol of the compound (B) per 1 mol of the epoxy resin (A). In the thermoplastic resin obtained by polymerizing the epoxy resin composition, the slope α in the absolute molecular weight range of 50,000 to 100,000 of the Mark-Houwink-Sakurada plot (MH plot) measured by light scattering gel permeation chromatography is 0.45 or more and 0.80 or less.
2. The epoxy resin composition according to claim 1, characterized in that The content of the polymerization catalyst (D) is 0.01 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the total amount of the epoxy resin (A) and the compound (B).
3. The epoxy resin composition according to claim 1, characterized in that It does not contain an organic solvent or, when containing an organic solvent, the content of the organic solvent is 0.01% by weight or more and 10% by weight or less of the epoxy resin composition, and the epoxy resin (A) and the compound (B) are uniformly dissolved.
4. An epoxy resin composition containing reinforcing fibers, characterized in that: The epoxy resin composition according to any one of claims 1 to 3 and a reinforcing fiber (F) are contained.
5. The epoxy resin composition containing reinforcing fibers according to claim 4, characterized in that: The reinforcing fibers (F) are continuous fibers.
6. The epoxy resin composition containing reinforcing fibers according to claim 4, characterized in that: Carbon fibers are contained as reinforcing fibers (F) in a ratio of 20 to 80% by weight.
7. A prepreg comprising the epoxy resin composition containing reinforcing fibers according to claim 4.
8. A fiber-reinforced plastic using the epoxy resin composition containing reinforcing fibers according to claim 4.
9. A fiber reinforced plastic using the prepreg according to claim 7.
10. A thermoplastic resin obtained from the epoxy resin composition according to any one of claims 1 to 3, wherein the thermoplastic resin has a slope α of 0.45 or more and 0.80 or less at an absolute molecular weight of 50,000 to 100,000 in a Mark-Houwink-Sakurada plot (MH plot) measured by light scattering gel permeation chromatography.
11. A prepreg comprising the thermoplastic resin according to claim 10 and reinforcing fibers (F).
12. A fiber-reinforced plastic comprising the thermoplastic resin according to claim 10 and reinforcing fibers (F).
13. A fiber reinforced plastic using the prepreg according to claim 11.
Citation Information
Patent Citations
Method for molding fiber-reinforced thermoplastic resin
JP2006321897A
Bisphenol f skeleton-containing phenoxy resin, manufacturing method therefor and resin composition using the same
JP2017171802A
Method for producing fiber-reinforced thermoplastic plastic and fiber-reinforced thermoplastic prastic
WO2004060981A1